International Jewish humanitarianism in the age of the Great War / Jaclyn Granick, Cardiff University. - Granick, Jaclyn, 1986- (Human rights in history., 2021)
In 1914, seven million Jews across Eastern Europe and the Eastern Mediterranean were caught in the crossfire of warring empires in a disaster of stupendous, unprecedented proportions. In response, American Jews developed a new model of humanitarian relief for their suffering brethren abroad, wandering into American foreign policy as they navigated a wartime political landscape. The effort continued into peacetime, touching every interwar Jewish community in these troubled regions through long-term refugee, child welfare, public health, and poverty alleviation projects. Against the backdrop of war, revolution, and reconstruction, this is the story of American Jews who went abroad in solidarity to rescue and rebuild Jewish lives in Jewish homelands. As they constructed a new form of humanitarianism and re-drew the map of modern philanthropy, they rebuilt the Jewish Diaspora itself in the image of the modern social welfare state.